Anthropological analyses of the Modern era-mummified human remains discovered in the Santa Maria del Monte sanctuary, Varese province, Italy - Larentis, Omar; Pangrazzi, Caterina; Tesi, Chiara; Fusco, Roberta (Medicina Historica, 2022)
Northeastern Italy preserves, although rarely, some naturally mummified remains from medieval and modern times. This study considers the remains from the province of Varese, with particular attention to those found in 2001 in a hypogeal burial chamber in the Santa Maria del Monte sanctuary in Varese, Lombardy. The materials, analyzed with classical methods of physical anthropology, consist of one head, one arm with the forearm, one forearm with the hand, a hand, a foot, and a lower limb with the foot. The analyses have allowed us to acquire new data regarding the use of funerary spaces during the medieval and modern ages, regarding the treatment of the body of the deceased and their alleged health status. Finally, the work helped in planning the subsequent analyses, to acquire a holistic view of all the variables of the bioarchaeological context.